2004
DOI: 10.4064/ap83-2-9
|View full text |Cite
|
Sign up to set email alerts
|

A note on Costara's paper

Abstract: Abstract. We show that the symmetrized bidisc2 cannot be exhausted by domains biholomorphic to convex domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 2 publications
0
24
0
Order By: Relevance
“…By (3), the equality κ Ωn (A; B) is equivalent to E * ,A (B) = 0. By property (8) in Proposition 3 and its proof, we have a matrix Y ∈ M n such that −Y A + AY = B. Then the mapping λ → e −λY Ae λY satisfies all the required properties.…”
Section: Nikolov Thomas and Zwonek Ieotmentioning
confidence: 99%
“…By (3), the equality κ Ωn (A; B) is equivalent to E * ,A (B) = 0. By property (8) in Proposition 3 and its proof, we have a matrix Y ∈ M n such that −Y A + AY = B. Then the mapping λ → e −λY Ae λY satisfies all the required properties.…”
Section: Nikolov Thomas and Zwonek Ieotmentioning
confidence: 99%
“…[3], [4], [7], [16], [11], [5] and others). It was shown that G 2 cannot be exhausted by domains biholomorphic to convex ones (see [7], [10]). So symmetrized bidisc delivers a counterexample to the above problem.…”
Section: Letmentioning
confidence: 99%
“…Let us show the implication (3) =⇒ (4). Suppose that Φ ν : D ν → G ν is a biholomorphic mapping and that G ν is convex.…”
Section: In Particular If D ⊂ C 2 Is a (1 2)-balanced Pseudoconvex mentioning
confidence: 99%
“…It is known that on G 2 holomorphically invariant distances are equal (see [1][2][3]), G 2 is not convex (see [2]), G 2 cannot be exhausted by domains which are biholomorphic to convex domains (see [4]), G 2 can be exhausted by domains which are strictly linearly convex (see [10]). Note that G 2 is a (1,2)-balanced pseudoconvex domain.…”
Section: Introductionmentioning
confidence: 99%